Establishing cross-discipline consensus on contraception, pregnancy and breast feeding-related educational messages and clinical practices to support women with rheumatoid arthritis: An Australian Delphi study - Briggs, Andrew; Jordan, J.; Ackerman, I.; Van Doornum, S. (BM J Group, 2016)
Objective: Recognising the need for a best-practice and consistent approach in providing care to women with rheumatoid arthritis (RA) in relation to (1) general health, (2) contraception, (3) conception and pregnancy, (4) breast feeding and (5) early parenting, we sought to achieve cross-discipline, clinical consensus on key messages and clinical practice behaviours in these 5 areas. Design: 3-round eDelphi study. In round 1, panellists provided free-text responses to open-ended questions about care for women with RA across the 5 areas. Subsequently, panellists refined and scored the synthesised responses, presented as metathemes, themes and detailed elements. Where =5% of panellists did not support a theme in a given round, it was removed. Setting: Panel of practicing Australian rheumatologists (n=22), obstetricians/obstetric medicine physicians (n=9) and pharmacists (n=5). Results: 34 (94.4%) panellists participated in all 3 rounds. The panel supported 18 themes across the 5 areas (support/strongly support: 88.2-100%) underpinned by 5 metathemes. Metathemes focused on coordination in information delivery, the mode and timing of information delivery, evidence underpinning information, engagement of the right health professionals at the right time and a non-judgemental approach to infant feeding. Themes included practices for primary prevention of chronic disease and their sequelae, the importance of contraception and planning pregnancy and breast feeding, close monitoring of medications, supporting mental wellbeing, managing disease activity and providing practical support for early parenting. Conclusions: A cross-disciplinary clinical panel highly supported key information and clinical practices in the care for women with RA across the continuum of contraception to early parenting within a whole-person, chronic disease management approach.